CYBER BULLYING DALAM ASPEK HUKUM - Thresia Hilda M.Y. Krey; Winna Amelia A. Senandi (JURNAL PENGABDIAN PAPUA, 2021)
The application of science and technology in the form of online counseling with a Zoom Meeting entitled "Cyber-Bullying in the Legal Aspects" was held at SMA Negeri 3 Jayapura and Youth and Youth Environment RT 005 / RW 007 Kota Baru Village, Abepura District, where most of the participants are children of age school and youth. This counseling aims to understand about Cyberbullying and its causes, as well as to know the various forms of cyber-bullying and its various legal aspects. The result of this activity was that the counseling conducted online through the Zoom Meeting was well received by the participants, with good response indicators from participants who enthusiastically gave weighty questions that were raised in the question session. In the end, education about the impact of cyber-bullying must be carried out with the target of school age children and teenagers as a preventive effort in dealing with cyber bullying to children and teenagers.Keywords: cyber, bullying, cyber-bullying, law, abepura